PENGARUH GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Yusti La Batta; Agus Endro Suwarno (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2022)
The firm value is a condition that has been achieved by a company and the firm value as a public trust and image of the company. The purpose of this study was to examine the effect of good corporate governance and it is effect on firm value empirical studies on automotive and component companies listed on the Indonesia Stock Exchange (IDX) in 2015-2020. The population used in study were companies and components listed on the Stock Exchange Indonesia (IDX) in 2015-2020. The type of data in this study is secondary data obtained from www.idx.co.id. The sampling method was purposive sampling according to the specified criteria. The number of samples collected was 57 samples. With 33 outliers it becomes 57 samples. So that only 12 companies are used that meet the criteria. The data that has been collected is analysed using data analysis first carried out by testing classical assumption then testing hypotheses. Classical assumption in this study using normality test, multicolinearity test, autocorrelation test and heteroscedastiscity test, while hypothesis testing uses multiple linear regression analysis with t test, f test and coefficient of determination test. The result of this study indicate that the audit commite variable affects the firm value while board of directors, managerial ownership, independent board of commissioners and leverage has no effect on firm value.